Cartilage‐Penetrating Framework Nucleic Acid Nanoparticles Ameliorate Osteoarthritis by Promoting Drug Delivery and Chondrocyte Uptake - Kui Huang; Qiumei Li; Huixuan Lin; Qian Shen; Yaping Wu; Taoran Tian; Chuan Ma; Sirong Shi; Jingang Xiao; Yunfeng Lin (Advanced Science, 2025)
Abstract Osteoarthritis (OA) is a chronic joint disease that causes a gradual deterioration of articular cartilage. A major challenge in OA treatment is the limited penetration and delivery efficiency of drugs to cartilage and chondrocytes due to the rapid clearance of drugs through synovial fluid in joints and the osmotic barrier of the cartilage extracellular matrix (ECM). To address this issue, a novel tetrahedral framework nucleic acid (tFNA)‐based nanomedicine delivery system (tFNA‐2WL) is first synthesized with excellent cartilage permeability and perfect chondrocyte endocytosis properties. After being loaded with ginsenoside Rb1 (Gin), the tFNA‐2WL&Gin complex not only penetrates the cartilage but also accumulates in the menisci, ligaments, and joint capsules, thus prolonging the residence time of Gin in OA rat knees. In vitro, tFNA‐2WL&Gin effectively promotes chondrogenesis, inhibits cartilage degradation by reducing apoptosis, and scavenges reactive oxygen species (ROS), outperforming free Gin. In OA rats, tFNA‐2WL&Gin restores gait, reduces osteophyte formation, inhibits synovial inflammation and hypertrophy, and protects cartilage from further damage more effectively than Gin and other nanomedicines. These results demonstrate the feasibility of tFNA‐2WL in improving the pharmacokinetics and efficacy of drugs and highlight the favorable curative effects of tFNA‐2WL&Gin for OA, offering a promising paradigm for translational medicine.